2007
DOI: 10.1002/app.26800
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of carbon nanofiber/linear low density polyethylene nanocomposites

Abstract: Crystallization behavior of LLDPE nanocomposites is reported in the presence of three types of carbon nanofibers (CNFs) (MJ,. During nonisothermal crystallization studies, all three crystalline melting peaks for LLDPE matrix were observed in the presence of PR-19 nanofibers (up to 15 wt % content), but only the high-and low-temperature peaks were observed in the presence MJ nanofibers. The broad melting peak at low-temperature became bigger, suggesting an increase in the relative content of thinner lamellae in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The peaks associated with (110), (200) and (020) planes of orthorhombic PE crystals appear at 2θ values of 21. 5°, 23.9°and 37.8°respectively for the pure PE sample [35]. For PE/CNT nanocomposites the expected peak at 2θ026°is not visible.…”
Section: Polymer Characterizationmentioning
confidence: 80%
“…The peaks associated with (110), (200) and (020) planes of orthorhombic PE crystals appear at 2θ values of 21. 5°, 23.9°and 37.8°respectively for the pure PE sample [35]. For PE/CNT nanocomposites the expected peak at 2θ026°is not visible.…”
Section: Polymer Characterizationmentioning
confidence: 80%
“…Vectran V400P is a random copolyester primarily of 1,4‐HBA and 4,6‐HNA, but contains other comonomers that provide selected meta‐linkages14; Table I displays its relevant properties 15. PyrografIII™ PR‐24‐PS carbon nanofibers (CNFs) were provided by Applied Science, Inc. (Cedarville, OH), and relevant properties are summarized in Table II 16, 17…”
Section: Methodsmentioning
confidence: 99%
“…where DH f is the normalized enthalpy of fusion, DH max is the enthalpy of fusion of 100% crystalline PP (207.1 J/g) and W poly is the weight fraction of PP in the blend. Effect of CNF on the crystallization process of polymers has been studied by various researchers [35][36][37][38][39][40][41][42][43][44]. Sandler et al [35] studied crystallization of CNT/PP and CNF/PP composites and observed that carbon nanomaterials act as nucleation sites in bulk samples and highly oriented composite films.…”
Section: Crystallization Behavior Of Composites: Dsc Analysismentioning
confidence: 99%